COMPARATIVE IN VITRO STUDIES ON PHYTOCHEMICAL AND ANTIBACTERIAL PROPERTIES OF ETHANOLIC EXTRACTS OF PLEUROTUS FLORIDA AND PLEUROTUS OSTREATUS - SRIDEVI .NEELAM; SUMMER SINGH (International Journal of Pharma and Bio Sciences, 2013)
The present investigation scientifically examined the phytochemistry and antibacterial potencies of ethanolic extracts of Pleurotus florida and Pleurotus ostreatus. Phytochemical analyses of the ethanolic extracts of the above pleurotus species revealed that there was moderate levels of terpenoids, tannins, steroidal glycosides and carbohydrates, flavonoids while alkaloids, carboxylic acids, Volatile oils, Cardinolides, Resins, Quinones, fatty acids and cynogenic glycosides were not detected. Generally, both extracts were effective against the isolates tested by agar well diffusion method, respectively. However, ethanolic extract of P.florida exhibited greater antibacterial activity than that of P.ostreatus and further produced growth inhibition of these isolates in broth. The results indicate that P. florida possesses antibacterial activity.